2012
DOI: 10.1098/rsbl.2011.1251
|View full text |Cite
|
Sign up to set email alerts
|

Functional diversity of bitter taste receptor TAS2R16 in primates

Abstract: In mammals, bitter taste is mediated by TAS2R genes, which belong to the large family of seven transmembrane G protein-coupled receptors. Because TAS2Rs are directly involved in the interaction between mammals and their dietary sources, it is likely that these genes evolved to reflect species-specific diets during mammalian evolution. Here, we investigated the sensitivities of TAS2R16s of various primates by using a cultured cell expression system, and found that the sensitivity of each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 15 publications
1
38
0
1
Order By: Relevance
“…Notably, the less responsive Asn172 is more common in individuals of African ancestry compared to those of European or Asian ancestry, the vast majority of whom carry the Lys172 allele. Similar small changes in TAS2R16 also explain differences in beta-glucopyranoside response across species (Imai, et al, 2012). …”
Section: Bitter Taste Differencesmentioning
confidence: 86%
“…Notably, the less responsive Asn172 is more common in individuals of African ancestry compared to those of European or Asian ancestry, the vast majority of whom carry the Lys172 allele. Similar small changes in TAS2R16 also explain differences in beta-glucopyranoside response across species (Imai, et al, 2012). …”
Section: Bitter Taste Differencesmentioning
confidence: 86%
“…Humans have high sensitivity to most b-glucoside agonists [25]. Macaques have 10-fold lower sensitivity to b-glucoside agonists in comparison with humans [26]. This study showed that TAS2R16 responses to b-glucosides also vary among lemurs ( figure 1; electronic supplementary material, figure S2).…”
Section: Discussionmentioning
confidence: 63%
“…Furthermore, we identified the first natural inverse agonist of TAS2R16 and the key residues responsible for inverse agonist recognition by site-directed mutagenesis. Anthropoids, including humans, recognize b-glucosides via TAS2R16 [26]. We found that lemurs (strepsirrhines) also recognize b-glucosides via TAS2R16 (figure 1), indicating that b-glucoside-sensitive TAS2R16 was present in the last common ancestor of primates and is conserved in extant primates.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Functional properties of the TAS2R38 receptor in colobines were evaluated using calcium imaging methods, as described previously [6,14,15]. To calculate responses to PTC, the amplitude of fluorescence was plotted against PTC concentration using IGOR Pro (WaveMetrics) and curves were fitted using nonlinear regression…”
Section: (D) Functional Assays Of Tas2r38mentioning
confidence: 99%